Anorectal angle at rest predicting successful sacral nerve stimulation in idiopathic fecal incontinence—a cohort analysis - Kollmann, Cathérine T. (Int J Colorectal Dis, 2020)
PURPOSE: Sacral nerve stimulation is an effective treatment for patients suffering from fecal incontinence. However, less is known about predictors of success before stimulation. The purpose of this study was to identify predictors of successful sacral nerve stimulation in patients with idiopathic fecal incontinence. METHODS: Consecutive female patients, receiving peripheral nerve evaluation and sacral nerve stimulation between September 2008 and October 2014, suffering from idiopathic fecal incontinence were included in this study. Preoperative patient’s characteristics, anal manometry, and defecography results were collected prospectively and investigated by retrospective analysis. Main outcome measures were independent predictors of treatment success after sacral nerve stimulation. RESULTS: From, all in all, 54 patients suffering from idiopathic fecal incontinence receiving peripheral nerve evaluation, favorable outcome was achieved in 23 of 30 patients after sacral nerve stimulation (per protocol 76.7%; intention to treat 42.6%). From all analyzed characteristics, wide anorectal angle at rest in preoperative defecography was the only independent predictor of favorable outcome in multivariate analysis (favorable 134.1 ± 13.9° versus unfavorable 118.6 ± 17.1°). CONCLUSIONS: Anorectal angle at rest in preoperative defecography might present a predictor of outcome after sacral nerve stimulation in patients with idiopathic fecal incontinence.